2020
DOI: 10.1007/s42832-020-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

High manure load reduces bacterial diversity and network complexity in a paddy soil under crop rotations

Abstract: Long-term application of chemical fertilizers causes soil degradation and nitrogen (N) loss, but these effects could be alleviated by organic fertilizers. In addition, crop rotation is a feasible practice to increase soil fertility, soil quality and crop yields comparing with monocultural cropping patterns. However, questions remain concerning how the soil microbiome responds to different manure application rates under crop rotations. Here, we collected soil samples from a rice-rape system to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 96 publications
4
22
0
Order By: Relevance
“…4). Our results are similar to the previous study by Liu et al (2020) which reported that 40 g/kg manure application rate decreased the stability of the bacterial network. Given the important role of environmental selection in community assembly, B. subtilis CY1 could speci cally select microbial populations with fewer interactions due to niche differentiation after organic fertilizer application.…”
Section: Discussionsupporting
confidence: 92%
“…4). Our results are similar to the previous study by Liu et al (2020) which reported that 40 g/kg manure application rate decreased the stability of the bacterial network. Given the important role of environmental selection in community assembly, B. subtilis CY1 could speci cally select microbial populations with fewer interactions due to niche differentiation after organic fertilizer application.…”
Section: Discussionsupporting
confidence: 92%
“…When the composition of soil microbial communities change, as they do when fertilization practices change, the microbial co-occurrence network changes as well (Ling et al 2016 ; Ramirez et al 2018 ). Network topology parameters have been used as biological indicators of the adaptability of microorganisms in response to fertilization disturbances (Ji et al 2020 ; Li et al 2020a ; Liu et al 2020a ). In our field test, we found that application of BIO (+ BIO) and HA (+ HA) reduced the modularity of the co-occurrence network of bacteria and fungi (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial network analysis has been widely used to explore microbial associations in complex environments ( 25 27 ). Although a cooccurrence network may not always reflect true ecological associations ( 28 , 29 ), it can help to understand how the complexity of microbial community changes in response to environmental factors ( 30 32 ). Recently, a directed network has been used to infer the directionality of associations in ecology networks ( 33 35 ).…”
Section: Introductionmentioning
confidence: 99%